Convergence and Challenges in the Management Policy of Vocational High School Education in Depok City, West Java, 2019–2023 - Ono Rusyono (International Journal Labs, 2026)
This study examines the convergence points and policy challenges in the management of Vocational High School (SMK) education in Depok City, West Java, during the 2019–2023 period. The research is motivated by the increasing demand for vocational education, which has not been adequately supported by school capacity, policy integration, and governance effectiveness. Using a qualitative descriptive approach and institutional analysis based on Rational Choice Institutionalism, this study analyzes the interactions among policy actors, including the central government, the West Java Provincial Government, the Depok City Government, vocational schools, and industry stakeholders. Data were collected through the analysis of laws, regulations, policy documents, and educational governance reports. The findings reveal several policy convergence points, including shared commitments to improving human resource quality, strengthening link-and-match programs with industry, curriculum development, teacher competency enhancement, educational quality assurance, and infrastructure improvement. However, significant policy challenges remain, including overlapping authority between provincial and municipal governments, limited school enrollment capacity, implementation issues related to Educational Operational Cost Assistance (BPOP), concerns regarding honorary teachers and PPPK recruitment, and weak industry partnerships. The study concludes that the effectiveness of vocational education management is strongly influenced by governance quality, particularly in terms of policy integration, inter-institutional coordination, accountability, stakeholder participation, and data-driven decision-making. An ideal governance model should emphasize policy integration, multi-stakeholder collaboration, and evidence-based educational planning to improve the quality and relevance of vocational education.